Revitalization of Biak Numfor Customary Dispute Resolution: Harmonization of the Criminal Justice System in Indonesia - Ar Rasyid, Yanuriansyah; Leni Sipra Helen Rahakbauw (Jurnal Ilmu Hukum Kyadiren, 2026)
Customary law is an option in resolving problems and disputes that occur in the indigenous people of Biak Numfor Regency. However, with the passage of Law Number 1 of 2023 concerning the Criminal Code, in deciding all problems, they still pay attention to the laws that live in society. Of course, this will cause an overlap between the two legal systems so that it requires revitalization and harmonization of the two laws. The research is a type of empirical research using the legal pluralism approach. As for this study, snowball sampling and purposive sampling are used in answering the problems raised. The results of the study show that customary law can be harmonized with positive law but with slight changes the difference between the two laws